1977
DOI: 10.1111/j.1439-0329.1977.tb00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids triggering coremia formation by Ceratocystis ulmi their occurrence and distribution in elm wood

Abstract: This paper reports the identification of fatty acids in elm wood and its active extractives triggering coremia formation, their distribution between bark, sapwood and heartwood of elms, and their occurrence in the mycelium of the pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…Les deux souches de C.jmbriata rkagissent de la mCme faqon que sur le bois de pin. Hubbes et al (1977) ont Ctabli que la formation d'organes de fructification pouvait Ctre influencCe par les substances contenues dans le bois. Pour prkciser l'action de ces substances sur le dkveloppement des corkmies et des pkrithkces, on incorpore au milieu nutritif, soit directement un extrait 2 l'eau, soit un extrait au chloroforme par lYintermCdiaire de rondelles de papier-filtre imprkgnCes de ces substances.…”
Section: Resultatsunclassified
See 1 more Smart Citation
“…Les deux souches de C.jmbriata rkagissent de la mCme faqon que sur le bois de pin. Hubbes et al (1977) ont Ctabli que la formation d'organes de fructification pouvait Ctre influencCe par les substances contenues dans le bois. Pour prkciser l'action de ces substances sur le dkveloppement des corkmies et des pkrithkces, on incorpore au milieu nutritif, soit directement un extrait 2 l'eau, soit un extrait au chloroforme par lYintermCdiaire de rondelles de papier-filtre imprkgnCes de ces substances.…”
Section: Resultatsunclassified
“…L'acide linoltique, stimulateur de cortmies chez C . ulmi et C. piceae, a kt6 identifit dans les extraits au chloroforme d'orme et de sapin (Hubbes 1975 (Hubbes et al 1977): 1,s g KH2P04, 1 g MgS04.7 H20, 0 , l g CaC12, 0 , l mg FeC13, 0,l mg MnS04, 0,l g NaHCO,, 1 g de glucose, 5 mg de pyridoxine, 5 mg de thiamine, 5 mg de biotine, 5 mg de nicotinamide, 5 mg de riboflavine, 232 mg d'acide fumarique, …”
Section: Introductionunclassified
“…In the DED pathogens, addition of linoleic acid to a complex growth medium (potato dextrose agar) was found to induce the formation of asexual spore bearing structures called synnemata (formerly known as coremia) (Hubbes 1975). Furthermore, Hubbes et al (1977) observed a high concentration of linoleic acid in elm sapwood and bark in June, and a decrease of this PUFA in heartwood. This would support the involvement of linoleic acid in the production of synnemata, since the latter are found in elm bark beetle breeding galleries under the bark (Hubbes et al 1977).…”
Section: R a F Tmentioning
confidence: 87%
“…The exact nature of the pigment produced in the stalk is not known, but some workers have hypothesized it is probably melanin (9,10). Linoleic acid, required for best synnema production on SPM (12), has been found in elm wood and associated with synnema production on that substrate (15). Therefore, linoleic acid, or a metabolite for this fatty acid, whether in elm wood or SPM, may be required for synnema and (or) pigment formation by C. ulmi.…”
Section: Discussionmentioning
confidence: 97%